Maternal Parvovirus B19 Infection Causing First-Trimester Increased Nuchal Translucency and Fetal Hydrops - Olivia Grubman; Farrah Naz Hussain; Zoe Nelson; Lois Brustman (Hindawi Limited, 2019)
This is a case report of a 31-year-old primigravida who was diagnosed with an asymptomatic acute parvovirus B19 infection in the second trimester of pregnancy and its suspected association with an increased nuchal translucency (NT) measurement. Parvovirus B19 is a single-stranded DNA virus that is cytotoxic to erythroid progenitor cells, causing inhibition of erythropoiesis. While maternal disease is usually mild, fetal infection can result in spontaneous abortion, aplastic anemia, nonimmune fetal hydrops, and fetal demise. This fetus had an increased NT of 3.2 mm at 11 weeks' gestation with a normal male karyotype and microarray analysis on chorionic villi sampling, in addition to a normal fetal echocardiogram at 15 weeks' gestation. The anatomy scan at 20 weeks' and 1-day gestation revealed fetal ascites, pleural effusion, and increased middle cerebral artery peak systolic velocity suspicious for fetal anemia. At this time, maternal serology for parvovirus was positive for IgM and IgG. Amniocentesis, cordocentesis, and intrauterine transfusion were performed. The amniocentesis revealed elevated parvovirus B19 DNA, quantitative PCR (2,589,801 copies/mL, reference range <100 copies/mL). The patient delivered a viable male fetus at 37 weeks' and 6-day gestation, without sequelae of the previously noted hydrops. Parvovirus B19 infection should be a consideration when evaluating increased NT and hydrops fetalis. It warrants close antepartum surveillance and possible intrauterine fetal transfusions. With prompt recognition, proper treatment, and surveillance, these patients can go on to achieve healthy term deliveries. Long-term outcomes of delivered infants require further study.